The difficulties that faced secondary school students in studying Mathematics during the Corona pandemic from the students' point of view - Al-khotani, Fardos Abdullah (Journal of Educational and Psychological Sciences, 2022)
The study aimed to know the difficulties that faced secondary school students in studying Mathematics during the Corona pandemic from the students' point of view. To achieve its objectives, the study relied on the descriptive analytical approach, which depends on collecting data from the study sample using a questionnaire. The study was applied to a random sample of secondary school students (first, second, third grade) in Yanbu, the number of the students are 1722. The results of the study showed that one of the most prominent difficulty that students face in technical aspects is the lack of the Internet connection, which leads to frequent interruptions in sound and image that makes the interactive with the teacher hard. The use of links frequently to move from one program to another during the lesson, and the large number of information and its overlap on the screen are the most important difficulties that hinder the student in understanding the course during the platform. The students feel shy asking about what they do not know in the class is one of the most important difficulties that the students face while learning Mathematics through the Microsoft Teams platform. Through the results, the researcher recommends conducting more studies similar to the current study for different educational stages and for other scientific courses.
Keywords: Mathematics; secondary school; Microsoft Teams; e-learning; Corona pandemic; difficulties